2003
DOI: 10.1890/02-0549
|View full text |Cite
|
Sign up to set email alerts
|

Community Composition and Photosynthesis by Photoautotrophs Under Quartz Pebbles, Southern Mojave Desert

Abstract: We used 16s rDNA sequences to identify novel species of cyanobacteria beneath translucent quartz pebbles in the desert pavement on an alluvial piedmont of the Coxcomb Mountains in the southern Mojave Desert, California, USA. Transmission of light, as measured with an integrating sphere, was about 0.08% beneath the thickest pieces of quartz (25 mm) harboring these hypolithic autotrophs. The photosynthetic rate ranged from 0.1 to 1.0 μmol·m−2·s−1 in the linear range of its response to light (PAR of 0–50 μmol·m−2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
119
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 20 publications
6
119
4
1
Order By: Relevance
“…The underside of rocks in climatically extreme deserts acts as a 'refuge' niche for photosynthetic microorganisms (defined as 'hypoliths') and their community (the 'hypolithon') (Pointing et al 2009;Chan et al 2012;Makhalanyane et al 2013bMakhalanyane et al , 2014Ramond et al 2015), where they photosynthesise at irradiance levels less than 0.1 % of the incident light (Schlesinger et al 2003). Here, the community is protected from abiotic stressors such as harsh ultraviolet radiation and wind scouring, with trapped moisture providing bioavailable liquid water.…”
Section: Hypolithsmentioning
confidence: 99%
“…The underside of rocks in climatically extreme deserts acts as a 'refuge' niche for photosynthetic microorganisms (defined as 'hypoliths') and their community (the 'hypolithon') (Pointing et al 2009;Chan et al 2012;Makhalanyane et al 2013bMakhalanyane et al , 2014Ramond et al 2015), where they photosynthesise at irradiance levels less than 0.1 % of the incident light (Schlesinger et al 2003). Here, the community is protected from abiotic stressors such as harsh ultraviolet radiation and wind scouring, with trapped moisture providing bioavailable liquid water.…”
Section: Hypolithsmentioning
confidence: 99%
“…3 Number of T-RFLP fragments per sample (fog-dominated vs. rainfall-dominated in hypolithic bacteria, soil bacteria and hypolithic cyanobacteria) presence of soluble salts (Cowan 2009). Moreover, moisture together with temperature and photosynthetically active radiation (PAR) are essential parameters that limit the growth and photosynthetic activity of hypolithic cyanobacteria (Schlesinger et al 2003;Warren-Rhodes et al 2006Tracy et al 2010). Both available liquid water, derived from rainfall (Warren-Rhodes et al 2006;Pointing et al 2007) or fog (Azua-Bustos et al 2011), and salinity (Thomas 2005;Pointing et al 2009) have been found to be key determinants of hypolithic communities.…”
Section: Effects Of the Environment And Spacementioning
confidence: 99%
“…All studies on hypoliths have indicated that these communities are most commonly dominated by photosynthetic cyanobacteria, with a taxonomically diverse heterotrophic component dominated by the phyla Acidobacteria, Actino-bacteria, Bacteroidetes and Proteobacteria (Schlesinger et al 2003;Warren-Rhodes et al 2006Pointing et al 2007Pointing et al , 2009Wood et al 2008;Chan et al 2012). However, the processes shaping the assembly of such communities are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…We targeted the hypolithic niche, ventral surfaces of quartz rocks embedded in desert soils, as this substrate is a ubiquitous feature of arid regions (Thomas, 1997) and a relatively inert substrate that supports development of microbial communities that are distinct from surrounding soils (Pointing et al, 2009). Hypolithic communities are thought to develop as a result of marginal gains in niche favorability in terms of moisture availability and possible thermal buffering (Schlesinger et al, 2003;Warren-Rhodes et al, 2006;Tracy et al, 2010), although micro-niche variability may occur between individual rocks (Tracy et al, 2010). Several studies have indicated that hypolithic communities comprise relatively simple communities dominated by cyanobacteria, with a heterotrophic component largely represented by the Acidobacteria, Actinobacteria, Bacteriodetes and proteobacterial phyla (Schlesinger et al, 2003;Warren-Rhodes et al, 2006Pointing et al, 2007Pointing et al, , 2009Wood et al, 2008;Wong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%